Fire Brigade Station, San Fernando, Trinidad, B.W.I. - (:unkn) unknown (W.A. Bonyun and Co., San Fernando, 2010)
A wooden fire station, located in San Fernando, the second largest town in Trinidad.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--San Fernando; Fire stations--Trinidad and Tobago; Architecture--Trinidad and Tobago